2010
DOI: 10.1002/eat.20864
|View full text |Cite
|
Sign up to set email alerts
|

Season of birth and disordered eating in a population‐based sample of young U.S. females

Abstract: Objective We used data from a population-based study of 9,039 adolescent and young adult females, followed prospectively since 1996 as part of the Growing Up Today Study (GUTS), to examine the relationship between season of birth and disordered eating in the U.S. Methods We tested whether the distribution of birth season and month differed for participants who had ever reported both underweight and dieting/weight concern symptoms (n=134) or both frequent bingeing and purging symptoms (n = 77) compared to oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The results of previous studies identified the month or season of birth as associated with type 1 diabetes, Parkinson's disease, anorexia nervosa, suicide, multiple sclerosis, schizophrenia, bulimia nervosa, disordered eating, and hip osteoarthritis . The increased risk of type 1 diabetes was investigated among young people aged 20 years and younger in the United States .…”
mentioning
confidence: 99%
“…The results of previous studies identified the month or season of birth as associated with type 1 diabetes, Parkinson's disease, anorexia nervosa, suicide, multiple sclerosis, schizophrenia, bulimia nervosa, disordered eating, and hip osteoarthritis . The increased risk of type 1 diabetes was investigated among young people aged 20 years and younger in the United States .…”
mentioning
confidence: 99%